Crosstalk between omega-6 oxylipins and the enteric nervous system: Implications for gut disorders? - Mantel, Marine; Derkinderen, Pascal; Bach-Ngohou, Kalyane; Neunlist, Michel; Rolli-Derkinderen, Malvyne (Frontiers in Medicine, 2023)
The enteric nervous system (ENS) continues to dazzle scientists with its ability to integrate signals, from the outside as well as from the host, to accurately regulate digestive functions. Composed of neurons and enteric glial cells, the ENS interplays with numerous neighboring cells through the reception and/or the production of several types of mediators. In particular, ENS can produce and release n-6 oxylipins. These lipid mediators, derived from arachidonic acid, play a major role in inflammatory and allergic processes, but can also regulate immune and nervous system functions. As such, the study of these n-6 oxylipins on the digestive functions, their cross talk with the ENS and their implication in pathophysiological processes is in full expansion and will be discussed in this review.